Biofertilization increases soil organic carbon concentrations: results of a meta-analysis - Berta Singla Just; Evan Alexander Netherton Marks; Laura Roquer-Beni; Laia Llenas; Sergio Ponsà; Rosa Vilaplana (International Journal of Agricultural Sustainability)
Protecting and building soil carbon has become a global policy priority, and novel agronomic fertilization practices may contribute to soil protection and climate-smart agriculture. The application of microbial inoculants (biofertilizers) is considered beneficial for soil and climate -smart agriculture. Therefore, an exhaustive meta-analysis of biofertilization studies was carried out worldwide to quantify the benefits of microbial inoculants on SOC concentration. Based on 59 studies and 267 observations, was found that biofertilizers significantly increased SOC concentration by an average of 0.44 g C kg−1 soil. All biofertilizer types were estimated to contribute positively to SOC (0.18–0.70 g C kg−1soil), but only cyanobacteria, mixtures of organisms, mycorrhizal fungi, and nitrogen fixers were statistically significant. In terms of crop type, results were significant and positive for cereals, fruits, legumes and root/tuber crops (0.44–0.82 g C kg−1soil). A significant positive linear relationship was observed between crop yield and SOC changes, supporting the notion that greater productivity helps explain SOC increases, accounting for 7% of the dataset variability. This study provides the first evidence from a global assessment that biofertilizer use is associated with an augmented terrestrial agricultural organic carbon sink contributing to soil protection and food security where climate-smart solutions are sought.